Supplementary Private Tutoring for Science Students of Higher Secondary (HSC) Level In Bangladesh: Perceived Factors, Causes And Challenges (Social Science Review, 2023)
Students use supplementary private tutoring for their education which is a worldwide phenomenon particularly in science education. The present study aimed to examine how household heads of Bangladesh perceive supplementary private tutoring factors, causes and challenges for science students of higher secondary (HSC) level. In this study, a survey questionnaire was administered with 200 randomly selected household heads of higher secondary science students in Mymensingh district of Bangladesh. To supplement the quantitative survey, the study also collected qualitative data from 12 higher secondary science teachers, 12 tutors as well as 20 students in two FGDs. The study shows that the level of income, education level and occupation of household heads may affect in taking the supplementary private tutoring for science students in Mymensingh. The main causes to take the tutoring are obtaining better result, making hard subjects easier, getting admission into better institutes, achieving local and foreign scholarships are mentioned as the causes of providing extra tutoring to their children. Moreover, lack of knowledgeable tutors, increasing initiatives for tutors and increasing expenditures for tutoring are identified as the major challenges. The findings of this study would have implication with policy initiatives and teaching learning practices in the science education development of Bangladesh.Social Science Review, Vol. 38(2), December 2021 Page 23-49